2020
DOI: 10.1186/s40729-020-00272-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of dynamic navigation compared to static surgical guide for dental implant placement

Abstract: Objectives To compare the accuracy of dynamic navigation (DN) with a static surgical guide (SSG) for dental implant placement and the influence factors such as the experience of the surgeon and the implant sites. Methods and materials A total of 38 implants, which underwent the dynamic navigation, and 57 implants which underwent a static surgical guide were enrolled in the retrospective study. Coronal deviation, apical deviation, and angular deviation were compared between the DN and SSG groups, along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 27 publications
7
55
1
2
Order By: Relevance
“…To date, few clinical studies on current methods have investigated the accuracy of implant positions in dynamic navigation [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Previously published data on the accuracy of dynamic navigation were analyzed in three systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few clinical studies on current methods have investigated the accuracy of implant positions in dynamic navigation [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Previously published data on the accuracy of dynamic navigation were analyzed in three systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor with a significant influence on accuracy is the type of implant [ 48 ]. In a retrospective study by Wu et al, no significant differences between the dynamic and static navigations were found at the coronal or apical endpoints or in the angular deviation when evaluating a total of 95 implants [ 41 ]. Yimari et al also reported a similar result in a randomized clinical trial [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise placement of implants is of great importance in survival of an implant-supported prosthesis [1]. Implant malposition was reported to be the most likely reason to cause peri-implantitis.…”
Section: Introductionmentioning
confidence: 99%
“… 54 Although much have been spoken about the accuracy of Navigation over conventional surgery, a recent study by Wu et al concluded that there are no significant statistical differences between Navigation assisted surgeries and conventional ones in terms of accuracy and postoperative outcomes. 55 …”
Section: Application In Oral and Maxillofacial Surgeriesmentioning
confidence: 99%